Tectonic geomorphology of the lake depressions in the Mongolian Altai mountains, western Mongolia - Enkhbold, Altanbold; Khukhuudei, Ulambadrakh; Seong, Yeong Bae; Yadamsuren, Gansukh; Batbold, Batzorig; Davaasuren, Davaadorj; Ganbat, Shuukhaaz; Tsedevdorj, Ser-Od; Bold, Bat; Badarch, Daariimaa; Ganbold, Byambabayar (Frontiers in Earth Science, 2025)
This study explores the tectonic geomorphology of lake depressions in the Mongolian Altai Mountains (MAM), focusing on three prominent lakes: Tolbo, Achit, and Uureg. These lakes are situated within tectonically active zones in the westernmost part of Mongolia, providing valuable insights into the interplay between geological processes and geomorphological evolution. The study investigates the structural characteristics and faults influencing lake depressions, utilizing satellite imagery, morphometric analysis, and geomorphological criteria interpretation. The morphometric analysis reveals significantly high HI (%) values for the Uureg, Achit, and Tolbo lake depressions, suggesting active tectonic movements in these regions. Additionally, the Smf, Bs, RSl, and Re indices support the evidence of ongoing tectonic processes. Since the northern MAM are located within a transpressional stress regime, the associated basins are expected to reflect this tectonic setting. Accordingly, all intermontane basins in the region are characterized as half-ramp, remnant low, or ramp basins. Each depression is shaped by different fault regimes, including thrust, strike-slip, and tilted thrust faults. These depressions are controlled by neotectonic processes associated with the Indian–Eurasian plate collision. Their dynamic nature underscores their significance as key tectonic features in the MAM. This case study deepens our understanding of the dynamic interplay between tectonics and lake depression formation in seismically active regions. It contributes valuable insights into the geomorphological evolution of mountainous landscapes.